PENGOLAHAN SAMPAH LOW DENSITY POLYETHYLENE (LDPE) DAN POLYPROPYLENE (PP) MENJADI BAHAN BAKAR CAIR ALTERNATIF MENGGUNAKAN PROTOTIPE PIROLISIS THERMAL CRACKING - Bow, Yohandri (KINETIKA, 2018)
The most popular of handling plastic waste up to now is with the 3R (Reduce, Reuse, Recycle). Hence the need for an innovation to reduce pollution resulting from plastic waste. One alternative way of handling plastic waste is to convert it into fuel or also called plastic pyrolysis process. Pyrolysis is the process of chemical decomposition of organic matter by heating without or little oxygen where the raw material will break the chemical structure into a gas phase. In this research, the design of plastic waste pyrolysis tool using thermal cracking method with infrared heating element. The raw materials used are Low Density Polyethylene (LDPE) and Polypropylene’s types plastic and the temperature that used in the reactor are 250°C, 300°C, and 350°C. The control variables are plastic waste mass, operating time, and pressure in the reactor. Of research results obtained in most product volume temperature 350oC as much as 68 ml plastic bins for Low Density Polyethylene with %yield of 6.34%. As for the plastic Polypropylene obtained also the most volume at 350oC as much as 70 ml with %yield 6.98%